2023
DOI: 10.1186/s13059-023-02877-1
|View full text |Cite
|
Sign up to set email alerts
|

The Network Zoo: a multilingual package for the inference and analysis of gene regulatory networks

Abstract: Inference and analysis of gene regulatory networks (GRNs) require software that integrates multi-omic data from various sources. The Network Zoo (netZoo; netzoo.github.io) is a collection of open-source methods to infer GRNs, conduct differential network analyses, estimate community structure, and explore the transitions between biological states. The netZoo builds on our ongoing development of network methods, harmonizing the implementations in various computing languages and between methods to allow better i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Using COBRA-corrected co-expression data from the same THCA study, we demonstrated that COBRA estimated batch-corrected, covariate-specific co-expression matrices that can be effectively used to estimate and compare GRNs between conditions. As both COBRA and PANDA are available through netZoo [Ben Guebila et al, 2023], we modified PANDA to allow COBRA correction to be incorporated into the analysis when the user supplies the parameter cobra_design_matrix . We found that the CEBP (CCAAT/enhancer-binding protein) and POU (Pit-Oct-Unc) families of transcription factors play important roles in THCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using COBRA-corrected co-expression data from the same THCA study, we demonstrated that COBRA estimated batch-corrected, covariate-specific co-expression matrices that can be effectively used to estimate and compare GRNs between conditions. As both COBRA and PANDA are available through netZoo [Ben Guebila et al, 2023], we modified PANDA to allow COBRA correction to be incorporated into the analysis when the user supplies the parameter cobra_design_matrix . We found that the CEBP (CCAAT/enhancer-binding protein) and POU (Pit-Oct-Unc) families of transcription factors play important roles in THCA.…”
Section: Discussionmentioning
confidence: 99%
“…COBRA is available in R and Python through the netZoo packages [Ben Guebila et al, 2023] netZooR v1.5 and netZooPy v0.9.16 (https://netzoo.github.io). We also provide tutorials in R and Python through Netbooks (http://netbooks.networkmedicine.org/) [Ben Guebila et al, 2022b].…”
Section: Code and Data Availabilitymentioning
confidence: 99%
“…By using the default parameters, we did not transform or filter the Z-Scores from the PANDA networks, as previously reported [ 21 , 23 ]. Then we compared weighted in-degree between the sexes by conducting a Wilcoxon rank sum test with continuity correction applied across each tissue and then made a Bonferroni-corrected p -value adjustment [ 43 ]. We also calculated the median of the weighted in-degree difference between the male and female drug metabolism genes for each tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Later, Bayesian inference approaches were used to construct highly probable molecular network structures [48,49]. More recently, due to the developments in AI/ML approaches, several automatic network inference tools have been proposed [50][51][52][53][54][55]. Although directly inferring networks from the data seem the most reliable way for further analyses and hypotheses generation, it is still very challenging to computationally extract true causality due to the lack of data and multimodal approaches.…”
Section: Constructing Molecular Networkmentioning
confidence: 99%